2021
DOI: 10.1155/2021/1481215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,25‐Dihydroxyvitamin D3 on Stem Cells from Human Apical Papilla: Adhesion, Spreading, Proliferation, and Osteogenic Differentiation

Abstract: Currently, it still remains a difficult problem to treat apical insufficiency of young permanent teeth resulted from pulp necrosis or periapical periodontitis. Previous studies have demonstrated that the treatment of revascularization using stem cells from apical papilla (SCAPs) results in increased root length and thickness of traumatized immature teeth and necrotic pulp. In this study, we investigated the role of 1,25-dihydroxyvitamin D3 in regulating the adhesion, spreading, proliferation, and osteogenic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Apart from osteogenic differentiation, calcitriol has a crucial impact on cellular growth. Many lines of evidence have indicated that 1,25(OH) 2 D 3 could contribute to promoting proliferation of bone ancestor cells, such as stem cells from the apical papilla and human bone marrow mesenchymal stem cells (43,56). Additionally, ANO5 is known to participate in proliferation of myoblasts and some cancer cells (57).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from osteogenic differentiation, calcitriol has a crucial impact on cellular growth. Many lines of evidence have indicated that 1,25(OH) 2 D 3 could contribute to promoting proliferation of bone ancestor cells, such as stem cells from the apical papilla and human bone marrow mesenchymal stem cells (43,56). Additionally, ANO5 is known to participate in proliferation of myoblasts and some cancer cells (57).…”
Section: Discussionmentioning
confidence: 99%